Experimental comparison of thermal comfort during cooling with a fan coil system and radiant floor system at varying space heights. (15th August 2018) - Cen, Chao; Jia, Yihong; Liu, Kuixing; Geng, Ruoxi
Abstract: With the development of the economy, architectural space forms and air conditioning systems have become more and more diverse. This paper presents a comparative study on thermal comfort in spaces of varying heights using a fan coil system and a radiant floor system for cooling in the "Comprehensive Experiment Platform of Variable Building Space" located in Tianjin, China. A total of 30 subjects participated the questionnaire survey under 8 different experimental conditions, and the indoor thermal environmental parameters were collected for these two systems at varying space height by instrument monitoring. Results indicated that space height had a significant effect on thermal comfort for both the fan coil system and the radiant floor system. The neutral temperature at space height of 3, 5, 7, and 9 m were 24.8 °C, 24.2 °C, 23.8 °C, and 23.5 °C, respectively. The neutral temperature gradually decreased with height of the ceiling when using a fan coil system, which means that participants had greater requirements for cooling at greater heights. In contrast, the neutral temperature at heights of 3, 5, 7, and 9 m were 23.5 °C, 23.8 °C, 24.1 °C, and 24.5 °C, respectively. The neutral temperature gradually increased when using the floor radiant system with increasing height, indicating that participants had lower requirements for cooling at greater heights. Furthermore, the results of this study demonstrate that the floor radiant system had an advantage over the fan coil system for thermal comfort in a space of greater height. Highlights: The neutral temperatures for the two systems were obtained by the laboratory experiment studies. The neutral temperatures of fan coil system decreased gradually with increasing space height. The neutral temperatures of the radiant floor system increased gradually with increasing space height. Fan coil systems provide better thermal comfort for low space height environments. Radiant floor systems provide better thermal comfort for high space height environments.